BEYOND SCHOOL LEADERSHIP: TRANSFORMING MADRASAH PRINCIPALS' LEADERSHIP TO FOSTER A CULTURE OF PEACE AMID THE CRISIS OF INTOLERANCE - Siti Lia Wafiroh; Sukarman Sukarman; Muhammad Khoiruddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2026)
The growing crisis of intolerance, bullying, and ideological polarization has expanded the role of madrasah principals beyond conventional school management toward fostering a culture of peace. This study aims to examine the transformation of madrasah principals’ leadership in promoting a culture of peace amid contemporary educational challenges and to identify strategic responses to intolerance within madrasah. A qualitative library research design was employed by analyzing academic literature, educational policies, and relevant regulations using content analysis. The findings reveal that effective leadership transformation requires principals to integrate transformational, moral, and peace-oriented leadership into institutional governance. This transformation is supported by the Regulation of the Minister of Education, Culture, Research, and Technology of the Republic of Indonesia Number 13 of 2022, which emphasizes safe, inclusive, and violence-free learning environments. However, principals continue to face challenges, including institutional resistance, digital intolerance, and ideological polarization. The study argues that moving beyond traditional school leadership toward peace leadership enables madrasah principals to strengthen institutional resilience, promote social cohesion, and cultivate a sustainable culture of peace. This study contributes a conceptual perspective that redefines the strategic role of madrasah principals as peace leaders in contemporary Islamic education.